Strategi Usaha Menengah Kecil Dan Mikro Bertahan Di Era Pandemi-19 - Hadion Wijoyo; Irfan Rizka Akbar (Mahesa Research Center, 2021)
Small and Medium Enterprises (MSMEs) are one of the businesses that really support economic activity, especially in conditions of the world economic crisis due to the Covid-19 pandemic. The increase in MSMEs shows how this sector is still a mainstay for the people's economy. The economic turnover is clearly visible in this sector. This is in line with the information conveyed by the Director General of Small and Medium Industry of the Ministry of Industry Euis Saedah that the prospects for small business businesses are still very good, given the very large population in Indonesia, around 250 million people. This research uses the literature study method, where the librarian study is all the efforts made by the researcher to gather information that is relevant to the topic or problem to be or is being researched. Email marketing is the most effective way to build connections with potential customers and turn them into loyal customers. Email marketing is also a personal way to communicate with customers.